A Rapid 3D-Modeling Method for Impeller of Wind Turbine. (August 2019) - Wu, Weimin; Zhou, Chuande; Liu, Jingcheng; Wang, Xiaomei; Yang, Yonggang
Abstract: It is a very important fundamental work that 3D-model of impeller for wind turbine can be achieved precisely, in order to enhance the credibility of CFD analysis in subsequent calculations. However, the current studies do not emphasize closely on the modeling with time-saving and high efficient. Therefore, one high efficient approach for geometric modeling of wind turbine impeller is proposed by this study, and the validity of logical framework and pseudo-code of each part correspondingly is confirmed through several applications upon modeling of impeller, with time-efficient to shape in the process-designed. Moreover, the validity concerning CFD solution is verified by CFD computations of wake of a wind turbine. Additionally, the high efficient approach is also suit for a wider spectrum in fluid machinery for the modeling of relevant entities, and especially for performing such optimal modeling associated with high efficiency, in terms of concise readjustment to grammar and related modeling operations in the logical framework proposed by this paper.